Enhancing English vocabulary acquisition among diploma students through magnetic compound word board games (Worsmithery Game) - Daneil, Imelia Laura; Tang, Howe Eng; Rijeng, Jacqueline Susan (2025)
Vocabulary acquisition is a crucial component of English language learning, especially for diploma students who need strong communication skills for academic and career purposes. However, traditional vocabulary teaching methods often rely on memorization, which may not engage students or support long-term retention. This study investigates the effectiveness of a magnetic compound word board game in enhancing English vocabulary acquisition among diploma students. The game involves combining two separate words to form a compound word (e.g., house + maid = housemaid), making the learning process more interactive and engaging. A total of 40 diploma students were divided into two groups: the experimental group used the magnetic board game during vocabulary lessons, while the control group followed a traditional textbook-based approach. Pre-tests and post-tests were administered to both groups, with results measured as percentages. The experimental group’s vocabulary scores improved from an average of 58% to 85%, showing a 27% increase. In contrast, the control group’s scores improved from 60% to 68%, an 8% increase. These results indicate that the use of a magnetic compound word game significantly improves vocabulary retention compared to conventional methods. The hands-on, visual, and interactive nature of the game likely contributed to better student engagement and understanding of word formation. This study suggests that incorporating educational games into English vocabulary instruction can be an effective strategy to support language learning among diploma-level students.